PENERAPAN NILAI-NILAI ISLAM DALAM PRAKTIK MANAJEMEN SUMBER DAYA MANUSIA (Studi Pebisnis Muslim pada Ayam Bakar Wong Solo Cabang Simongan) - Isti’adzah, Izzah; Mas’ud, Fuad (Faculty of Economics and Business Diponegoro University, 2017)
Islam-based management is a management practice which implements Islamic values in management and is currently started to be applied in many companies or businesses. However, due to limited of knowledge of the managers and employees to the values of Islam will lead to the ineffective application of the management practice. This study analyzed the extent to which the relationship and the role of Islamic values influence the aspects of a business. The purpose of the study is to analyze the extent to which the understanding of the owner, manager, and employees regarding Islamic values applied in management. This study also analyze the practice of the management based on Islam at the company and analyze the motivation of employees. The method used is a qualitative method with case study approach. The reasons for selecting this method is that research can focus and can be done in depth to determine the management practices of Islam based on Ayam Bakar Wong Solo Branch Simongan. The results showed that the owners and business practitioners have a good understanding associated with Islamic values which are implemented at the workplace. The Islamic values are implemented within human resources management practices such as human resource planning, recruitment, selection, employment contracts, training and development, performance appraisal and compensation.